Analisis Penerapan Akuntansi Pada Usaha Toko Pupuk Di Kecamatan Abuki Kabupaten Konawe - Vicha, Wiwin Sultraeni, Ilham Akbar Garusu, Rafida Bangki (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
The fertilizer store business plays an important role in the agricultural sector, especially in rural areas that rely heavily on agriculture as a primary means of fulfilling national food needs. This research aims to understand the application of accounting in fertilizer store businesses in the Abuki district, Konawe Regency. A qualitative descriptive approach was used in this research, with data collection methods including interviews and documentation. The results of this study show that most fertilizer store owners have not fully implemented accounting practices in accordance with the SAK EMKM accounting standards. Transaction recording is still done simply and does not cover all business components, due to a lack of understanding by business owners about the importance of accounting in business management. Therefore, there is a need for socialization and training on simple accounting to improve financial management quality in fertilizer stores, thereby supporting better business development in the future.